2021
DOI: 10.1021/acsami.0c19174
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Limit of Ge Dopants in AlGaN: A Chemical and Microstructural Investigation Down to the Nanoscale

Abstract: Attaining low resistivity AlxGa1−xN layers is the keystone to improve the efficiency of light emitting devices in the ultraviolet spectral range. Here, we present a microstructural analysis of AlxGa1−xN:Ge samples with 0 ≤ x ≤ 1, and nominal doping level in the range of 10 20 cm 3 , together with the measurement of Ge concentration and its spatial distribution down to the nm scale. AlxGa1−xN:Ge samples with x ≤ 0.2 do not present any sign of inhomogeneity. However, samples with x > 0.4 display µm-size Ge crys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…The “memory effect”, if not properly managed, will have even more severe repercussions on the growth of heavily doped heterostructures, such as tunnel junctions, where precise control of doping profiles and interfaces determines the device performance. For thick, heavily doped GaN:Ge layers, it also leads to Ge precipitates, as reported before by others [ 25 ] and observed also for our crystals.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The “memory effect”, if not properly managed, will have even more severe repercussions on the growth of heavily doped heterostructures, such as tunnel junctions, where precise control of doping profiles and interfaces determines the device performance. For thick, heavily doped GaN:Ge layers, it also leads to Ge precipitates, as reported before by others [ 25 ] and observed also for our crystals.…”
Section: Discussionsupporting
confidence: 90%
“…In spite of that, early efforts to obtain GaN:Ge by plasma-assisted MBE reported the formation of both Ge and Ge 3 N 4 precipitates for concentrations exceeding 4 × 10 20 atoms/cm 3 as reported by Hageman et al [ 24 ]. More recently, the doping limit for plasma-assisted MBE of AlGaN:Ge was identified by Bougerol et al [ 25 ]. The authors claim to have found the pronounced solubility limit for germanium in AlGaN layers with Al contents higher than 0.2, leading to the formation of Ge crystallites and Ge inclusions, mainly formed near defects or metal droplets on the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To attain doping concentrations beyond the Mott transition (≈10 19 cm –3 ), the use of Ge is preferred, due to the proximity of the Ge–N and Ga–N binding energies. However, the solubility limit for Ge in GaN is attained around 4 × 10 20 cm –3 , , and it decreases with the incorporation of Al in the material …”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, laser-assisted atom probe tomography (La-APT) was widely employed in order to analyze the composition of dielectrics and semiconductors at the nanometer scale, including dopant atom distribution and chemical mapping of defects, providing fundamental new insights into the atom-scale mechanisms taking place during material growth and device fabrication (Grenier et al, 2014; Rigutti et al, 2016; Di Russo et al, 2017 a , 2017 b , 2020 a , 2020 b ; Dumas et al, 2019; Amichi et al, 2020; Cuduvally et al, 2020; Dimkou et al, 2020; Bougerol et al, 2021; Dumas et al, 2021). Such local quantitative analyses require to measure elemental composition with high accuracy (i.e., sensitivity in the range of 10 18 –10 19 cm 3 ) and near-atomic scale resolution.…”
Section: Introductionmentioning
confidence: 99%